Management of the infertile couple: an evidence-based protocol - Kamel Remah M (BMC, 2010)
Abstract Background Infertility is defined as inability of a couple to conceive naturally after one year of regular unprotected sexual intercourse. It remains a major clinical and social problem, affecting perhaps one couple in six. Evaluation usually starts after 12 months; however it may be indicated earlier. The most common causes of infertility are: male factor such as sperm abnormalities, female factor such as ovulation dysfunction and tubal pathology, combined male and female factors and unexplained infertility. Objectives The aim of this study is to provide the healthcare professionals an evidence-based management protocol for infertile couples away from medical information overload. Methods A comprehensive review where the literature was searched for "Management of infertility and/or infertile couples" at library website of University of Bristol (MetaLib) by using a cross-search of different medical databases besides the relevant printed medical journals and periodicals. Guidelines and recommendations were retrieved from the best evidence reviews such as that from the American College of Obstetricians and Gynaecologists (ACOG), American Society for Reproductive Medicine (ASRM), Canadian Fertility and Andrology Society (CFAS), and Royal College of Obstetricians and Gynaecologists (RCOG). Results A simple guide for the clinicians to manage the infertile couples. Conclusions The study deploys a new strategy to translate the research findings and evidence-base recommendations into a simplified focused guide to be applied on routine daily practice. It is an approach to disseminate the recommended medical care for infertile couple to the practicing clinicians.